(untitled) (Research, Society and Development, 2025)
This study aimed to develop and evaluate bakery products enriched with flour obtained from the mesocarp of baru (Dipteryx alata Vog.), a native fruit of the Brazilian Cerrado. Cake and bread were formulated with the addition of this flour, and their proximate composition, texture, and sensory acceptance were analyzed. The enriched cake showed a significant increase in protein (10.37 g/100 g) and fiber (4.20 g / 100 g) content, along with lower hardness and chewiness, improving the texture. Sensory evaluations indicated that it was well accepted by the panelists. The bread formulation also showed increased protein (18.38 g / 100 g) and fiber (1.03 g / 100 g) levels; however, it exhibited greater hardness and reduced elasticity, cohesiveness, and resilience, compromising its structure and sensory acceptance. The results suggest that baru mesocarp flour has high potential as a functional ingredient, particularly in cakes, by enhancing nutritional value.